Cancer epigenetics - Tollefsbol, Trygve O (CRC Press, 2009)
During the past few decades, it has become increasingly apparent that heredity is not the sole determining factor in disease development, such as cancer. This landmark work covers a wide array of aspects in the relatively new area of epigenetics, ranging from its role in the basic mechanisms of tumorigenesis, to the newest epigenetic drugs being developed and used for cancer therapy. Cancer Epigenetics presents in-depth discussions of DNA methylation alterations, histone and RNA modifications, and nucleosome remodeling, which are all intimately involved in the formation of tumors. It also analyzes metabolic influences on cancer epigenetics and advances in epigenetic cancer gene therapy. Discusses the Latest Advances in the Role of Epigenetics in Tumor Initiation, Progression, and Metastasis With stand-alone chapters written by research pioneers in the field, this definitive resource covers— DNA methylation and cancer Histone modifications in cancer Emerging areas of cancer epigenetics Epigenetics in the diagnosis, prognosis, and therapy of cancer Future directions in epigenetic cancer research Bringing together different topics into a single compilation, this text is a prime resource for those with interests ranging from the basic mechanisms of tumor biology to cancer therapy. It also serves as a core textbook for advanced courses with a focus on genetic diseases, molecular biology, and/or cancer. This seminal work answers the call for a thorough and authoritative reference that covers the critical and contemporary aspects of this revolutionary field.
Keywords: epigeneze genetická; onkologie; nádory; Neoplasms; histony; Epigenesis, Genetic; DNA modifikační methylasy; DNA Modification Methylases; Histones; genetika, lékařská genetika